Utilization of CO2 captured from the coal-fired flue gas by catalyst - adsorption method for growing Spirulina having high nutritive value - Kim, Dang Dinh; Kim Anh, Bui Thi; Cu, Nguyen Tien; Minh Nguyet, Tran Thi; Hong, Dang Diem; Chinh, Mai Trong; Thom, Dang Thi; Chuyen, Nguyen Minh; Oanh, Doan Thi (Academia Journal of Biology, 2013)
CO2 is very important greenhouse gas and burning coal process produces mainly CO2 and other accompanied gases (NOx, SOx, HxCy, CO,…). The microalgae and cyanobacteria are capable of using free CO2 and bicarbonate ions as a source of inorganic carbon during photosynthesis. In this study, CO2 gas in range of 4-7% was captured selectively by a special equipment using a catalyst-adsorption system and stored for growing Spirulina platensis after effective removing the accompanied gases presented in the flue gas. The obtained research results indicated that the recuperated CO2 content was proved to be good carbon source for growth of a Cyanobacterium Spirulina platensis. The growth of Spirulina platensis in the modified Zarrouk’s medium supplied with this CO2 source was highest while biomass quality of Spirulina platensis using CO2 collected from the coal-firing process was almost equivalent to that of the Cyanobacterium grown in nutritive medium supplied with pure CO2 source.